Analisis unsur budaya dan arsitektural di Masjid Jamek Sultan Ibrahim, Muar, Johor - Shahridzal, Nuralyia Natasha binti; Ahmad, Hakimi bin (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The Sultan Ibrahim Mosque serves as the Muar neighborhood’s ‘Jewel’ is situated conterminous to the Sultan of Johor’s Palace located by the Muar River. Despite Masjid Jamek Sultan Ibrahim’s being a heritage structure in Muar with the influence of Victorian architecture combines with local influence, there is a lack of in-depth analysis of the traditional Javanese cultural elements with tangible and intangible material culture resulted in the knowledge that contributes to the mosque’s character and its function in the community. The objective is to analyze and identify the cultural fundamental features of the mosque that exhibit Javanese influences and to explore the mosque’s role in fostering interfaith discussion and community outreach, as well as how it affects the social and cultural fabric of the community. A theoretical framework based on cultural studies and heritage studies, that include cultural construction, cultural transmission, and heritage management. To focus on the study to identify the possible advantages of preserving and promoting the cultural components of this mosque, such as fostering religious dialogue, improving cultural tourism, and enhancing the feeling of cultural identity in the community. Methods for this research include thematic analysis and anthology on the case study site to gain and gather more information. The findings of this study will provide Javanese traditional cultural elements of this mosque valuable perceptivity. This study can increase the sense of cultural identity in the community and foster greater social cohesiveness